Minimally Invasive Treatment of Displaced Proximal Humeral Fractures in Patients Older Than 70 Years Using the Humerusblock. (17th November 2016) - Bogner, Robert; Ortmaier, Reinhold; Moroder, Philipp; Karpik, Stefanie; Wutte, Christof; Lederer, Stefan; Auffarth, Alexander; Resch, Herbert
Abstract : Background. Surgical treatment of proximal humeral fractures (PHF) in osteoporotic bone of elderly patients is challenging. The aim of this retrospective study was to evaluate the clinical and radiological outcome after percutaneous reduction and internal fixation of osteoporotic PHF in geriatric patients using the semirigid Humerusblock device. Methods. In the study period from 2005 to 2010, 129 patients older than 70 years were enrolled in the study. After a mean follow-up of 23 months, a physical examination, using the Constant-Murley score and the VAS pain scale, was performed. Furthermore radiographs were taken to detect signs of malunion, nonunion, and avascular necrosis. Results. The recorded Constant-Murley score was 67.7 points (87.7% of the noninjured arm) for two-part fractures, 67.9 points (90.8%) for three-part fractures, and 43.0 points (56.7%) for four-part fractures. In ten shoulders (7.8%) loss of reduction and in four shoulders (3.1%) nonunion were the reason for revision surgery. Avascular humeral head necrosis developed in eight patients (6.2%). Conclusions. In two- and three-part fractures postoperative results are promising. Sufficient ability for the activities of daily living was achieved. In four-part fractures the functional results were less satisfying regarding function and pain with a high postoperative complication rate. In those patients other treatment strategies should be considered. Study design. Therapeutic retrospective case series (evidence-based medicine (EBM) level IV).